PC0006 Impact of physician preferences for homeopathic or conventional medicines on patients with muskuloskeltal disorders: Results from the EPI3-MSD cohort. (23rd January 2014) - Rossignol, M.; Bégaud, B.; Engel, P.; Avouac, B.; Lert, F.; Rouillon, F.; Bénichou, J.; Massol, J.; Duru, G.; Magnier, A.-M.; Guillemot, D.; Grimaldi-Bensouda, L.; et al.
Abstract : Background: Musculoskeletal disorders (MSDs) are a leading reason for consultation in primary care. As these disorders tend to become chronic, available treatments are largely symptomatic in nature explaining in part the preferences of physician and patients for homeopathy and complementary and alternative medicine (CAM). There is a paucity of information on how use of homeopathy and CAM modifies patients' exposure to conventional drugs used in MSDs, non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics. A major obstacle to such studies is the lack of a comparable non-CAM users group. In France, homeopathy is the most frequently used type of CAM and is only prescribed by physicians, mostly general practitioners (GP), and reimbursed by the National Health Insurance as with all other conventional drugs. Objectives: The objective of this study was to assess the effect of physician practicing preferences (PPP) in primary care for homeopathy (Ho), CAM with conventional medicine (Mx) or exclusively conventional medicine (CM) on patients with musculoskeletal disorders, with reference to clinical evolution, medicines consumption, side effects and loss of therapeutic opportunity. Methods: The EPI3-MSD study was a nationwide observational cohort of a representative sample of general practitioners (GPs) and their patients in France. Recruitment of GPs was stratified by PPP, which was self-declared. Diagnoses and comorbidities were recorded by GPs at inclusion. Patients completed a standardized telephone interview at inclusion, one, three and twelve months, including MSD-functional scales and medicines consumption. Results: A total of 1153 MSD patients were included in the three PPP groups. Patients did not differ between groups except for chronicity of the MSD (>12 weeks duration), which was higher in the Ho group (62.1%) than in the CM and Mx groups (48.6% and 50.3%, respectively). The twelve-month evolution of specific functional scores was identical between the three groups after controlling for baseline score (p>0.05). After adjusting for propensity scores, NSAID use over 12 months was almost half in the Ho group (OR, 0.54; 95%CI, 0.38-0.78) as compared to the CM group, no difference was found in the Mx group (OR, 0.81; 95% CI: 0.59–1.15). In the Ho group, the number of prescriptions per 100 patient-years was 63.1 and 59.0 for non-chronic and chronic MSD patients, respectively; compared to 102.4 and 117.6 in the CM group (both significant at p<0.05). Conclusions: MSD patients seen by homeopathic physicians showed a similar clinical evolution while being less exposed to NSAIDs as compared to patients seen in CM practice, with potentially less NSAID-related adverse events and no loss of therapeutic opportunity. Disclosure of Interest: None Declared